Investasi Sport Tourism sebagai Pengungkit Pembangunan Daerah Berkelanjutan di Kabupaten Bandung (Analisis Pentahelix Dan Multiplier Effect) - Prayoga, Indra Aditya; Kurnia, Encep (Neolectura, 2025)
This study aims to analyze the contribution of large-scale investments in the sport tourism sector to regional development in Bandung Regency, focusing on the relationship between investment policies, governance, and community participation in achieving sustainable development. A qualitative-descriptive approach was employed using a case study strategy, incorporating in-depth interviews, field observations, and document analysis of official government reports and relevant secondary data. The findings reveal that investments in sports infrastructure and the organization of national-scale sporting events have generated significant multiplier effects on the local economy, including the growth of micro-enterprises, increased community income, and regional economic diversification. However, the effectiveness of sport tourism implementation is largely influenced by participatory governance, consistent policy alignment, and the integration of sports, tourism, and creative economy sectors. This study highlights the importance of the pentahelix collaboration model—engaging government, academia, businesses, communities, and media—in strengthening the sustainability and efficiency of sport tourism investment. Theoretically, this research contributes to the literature on regional development by integrating the concepts of economic multiplier effects and sustainable development. Practically, the findings offer policy recommendations for local governments to optimize sport tourism potential through inclusive, competitive, and community-oriented investment strategies.